Terrorism – the Dark Side of Demographic Dividend. A Case Study of Pakistan - Zahid, Farhan; Khan, Adeem (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2016)
Demographic dividend could be considered as a corollary to demographic transition. Because of the shift in demographics with respect to mean age over a period of time more people fall under the age bracket of 15-64 than below 15 and above 64. Fortunately, Pakistanis considered to be one of these states experiencing the phenomenon of demographic dividend. Pakistan is also one the worst victims of terrorism, which can be regarded as the dark side of the demographic explosion. There may be many other fallouts such as rise in crime, local feuds, civil war and other forms of political violence but in fragile states with ungoverned territories, the demographic disproportions vis-i-vis resources may pave the way for terrorism. This would be an ideal situation terrorist recruitment and size of terrorist organizations would also increase vis-i-vis the population growth. The Islamist terrorist organizations would capitalize on this upcoming situation as they have the required trained cadres and infrastructure to reap the benefits of the demographic dividend. In case the country fails to reap the benefits of demographic dividend then the terrorist organizations would.

Pakistan postrzegany jest jako jedno z tych państw, które w największym stopniu doświadcza dywidendy demograficznej. Jest także swoistą ofiarą terroryzmu, który stanowi “ciemną stronę” eksplozji demograficznej. Mogą pojawić się oczywiście inne negatywne zjawiska, takie jak wzrost przestępczości, korupcja, konflikty wewnętrzne i inne formy przemocy politycznej, lecz w państwach kruchych dysproporcje demograficzne mogą nasilić zjawisko terroryzmu.
Terroryzm - mroczna strona dywidendy demograficznej na przykładzie Pakistanu
Keywords: Demographic dividend; Pakistan; terrorism; Pakistan; dywidenda demograficzna; terroryzm